(untitled) (Asian Education Studies, 2020)
The research article deals with learners’ beliefs, choices, expectations and perception of some important sub-skills for improving their language abilities. The sample consists of 117 learners are : 33 fourth year major English degree, 56 second year English diploma from Eritrea Institute of Technology, Mai Nefhi, Eritrea and 28 mixed groups from the University of Nyala, Sudan. A questionnaire that consists of 43 items with five options was prepared, distributed, collected, processed and analyzed. In general the responses are 37.43% extremely important, 35.72% very important, 19.80% important, 4.35% less important, 1.6% least important and 2.16% no response. On the basis of their preferences, the learners also ranked the sub-skills from first to forty-third such ‘expressing what you want to say first, knowledge of vocabulary second, listening to pronunciation/intonation/stress patterns of English third, etc. (Please refer to Table 2 and appendix A).